Fulminant hepatic failure caused by herbal supplies - Genário Oliveira Santos Júnior; Raymundo Paraná Ferreira Filho; Liana Machado de Codes Foulon; Lúcia de Araújo Costa Beisl Noblat (Universidade de São Paulo, 2018)
The consumption of botanicals for therapeutic purposes has increased significantly in recent years. Drug-induced liver disease (DILI) is a frequent cause of acute liver injury, around 50% in the United States, and about 1% is secondary to the use of phytotherapeuticals and herbal supplies. Ruellia bahiensis, a plant species of the Acanthaceae family, is a tropical plant distributed in Northeastern Brazil. In folk medicine in the state of Bahia, the species is known as "mãe-boa" and is commonly used. L.S.S, a 23-year old, female, patient was admitted at University Hospital of Bahia-Brazil with signs and symptoms of acute hepatitis. She had made daily use of an herbal supply popularly known as "mãe-boa" for at least two years prescribed by a physician. Diagnostic investigation was negative for viral and autoimmune hepatitis, leptospirosis, dengue, and CMV (cytomegalovirus). The patient had to undergo liver transplantation. Explant revealed massive hepatic necrosis. According to histological findings, and after exclusion of other etiologies, liver damage was assigned to herbal supply. The prolonged use of Ruellia bahiensis infusions may have caused the liver dysfunction.